Research progress on polysaccharide/protein hydrogels: Preparation method, functional property and application as delivery systems for bioactive ingredients. (September 2021) - Liu, Kang; Chen, Ying-Ying; Zha, Xue-Qiang; Li, Qiang-Ming; Pan, Li-Hua; Luo, Jian-Ping
Graphical abstract: Highlights: The preparation method and functional property of hydrogels were summarized. Applications of hydrogels as delivery systems for bioactive ingredients were reviewed. Encapsulation and release mechanisms of bioactives by hydrogels were discussed. Abstract: Some bioactive ingredients in foods are unstable and easily degraded during processing, storage, transportation and digestion. To enhance the stability and bioavailability, some food hydrogels have been developed to encapsulate these unstable compounds. In this paper, the preparation methods, formation mechanisms, physicochemical and functional properties of some protein hydrogels, polysaccharide hydrogels and protein-polysaccharide composite hydrogels were comprehensively summarized. Since the hydrogels have the ability to control the release and enhance the bioavailability of bioactive ingredients, the encapsulation and release mechanisms of polyphenols, flavonoids, carotenoids, vitamins and probiotics by hydrogels were further discussed. This review will provide a comprehensive reference for the deep application of polysaccharide/protein hydrogels in food industry.